2008
DOI: 10.1016/j.pneurobio.2007.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin: Behavioral roles of an “original” neuropeptide

Abstract: Vasopressin (Avp) is mainly synthesized in the magnocellular cells of the hypothalamic supraoptic (SON) and paraventricular nuclei (PVN) whose axons project to the posterior pituitary. Avp is then released into the blood stream upon appropriate stimulation (e.g., hemorrhage or dehydration) to act at the kidneys and blood vessels. The brain also contains several populations of smaller, parvocellular neurons whose projections remain within the brain. These populations are located within the PVN, bed nucleus of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
418
0
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 427 publications
(434 citation statements)
references
References 324 publications
(368 reference statements)
10
418
0
6
Order By: Relevance
“…However, together our results suggest that Tll and Atro are part of the transcription module that controls the activity of PI neurons affecting the release of neuropeptides that regulate aggressive behaviour. Our findings in flies suggest that three mechanisms that are involved in the regulation of aggression in mammalstranscriptional control by Nr2e1 (refs 19,27-29), electrical [33][34][35] or optogenetic 55 stimulation of hypothalamic neurons and neuropeptide release from the neurosecretory cells of the hypothalamus 44 -may in fact be a single mechanism that may represent a core aggression regulatory mechanism in all animals.…”
Section: Article Nature Communications | Doi: 101038/ncomms4177mentioning
confidence: 79%
See 4 more Smart Citations
“…However, together our results suggest that Tll and Atro are part of the transcription module that controls the activity of PI neurons affecting the release of neuropeptides that regulate aggressive behaviour. Our findings in flies suggest that three mechanisms that are involved in the regulation of aggression in mammalstranscriptional control by Nr2e1 (refs 19,27-29), electrical [33][34][35] or optogenetic 55 stimulation of hypothalamic neurons and neuropeptide release from the neurosecretory cells of the hypothalamus 44 -may in fact be a single mechanism that may represent a core aggression regulatory mechanism in all animals.…”
Section: Article Nature Communications | Doi: 101038/ncomms4177mentioning
confidence: 79%
“…Our rationale was based on the idea that conserved transcription modules-which consist of a transcription factor with conserved co-factors, conserved binding site and conserved targets-exist in the evolutionarily conserved control of development 15 and behaviour 16,18 . We found that a conserved transcription factor, Tll, and its conserved co-repressor, Atro, indeed affect aggression in flies and that this transcriptional repressor complex acts through a set of adult neurosecretory cells known as the PI, which has remarkable similarity to the mammalian hypothalamus 31 , a brain region known for its critical role in the control of aggressive behaviour in mammals [33][34][35]44 . Moreover, we found that electrical activation of these neurons is sufficient to cause an increase in aggression in flies, just like electrical stimulation of the hypothalamus does in mammals [33][34][35] .…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations